The Impact of the United States of America and China Export Rate Setting on Wealth and Liquidity of Shareholders - Helma Malini; Herry Giovandi (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
The US-China trade war began in 2017 when both countries-imposed tariffs onproduct imports. The purpose of this study is to examine the effect of policy onshareholder prosperity (as measured by variable abnormal returns) and stock liquidity (asmeasured by variable volume trading activity) on the Indonesian Stock Exchange. Thedescriptive statistics, normality test, and paired sample t-test are used to analyse the datawhere sources of data in this study are secondary data. Secondary data in this study takenfrom the daily price of shares listed on the Indonesia Stock Exchange, especially stockslisted in LQ45 index from 27th June 2018 – 17th July 2018. The findings of this studyindicate that the United States and China's export-import tariff policies on 6th July 2018 donot have significant differences in terms of return and average trading volume. This meansthat the policy contains no information that could be used to influence investor decisionson the Indonesian Stock Exchange.